PENGARUH PANDEMI COVID-19 DAN NILAI TUKAR TERHADAP INDEKS HARGA SAHAM GABUNGAN DI BURSA EFEK INDONESIA - Ni Luh Putu Sri Agustini; I Putu Fery Karyada; Putu Nuniek Hutnaleontina (UNHI Press, 2023)
The purpose of this research is to analyze how changes in positive covid-19 cases, as well as exchange rates, affect the Composite Stock Price Index in Indonesia. The variables in this study were daily data from the Indonesia Stock Exchange's Composite Stock Index, positive Covid-19 cases, and exchange rates from March 2, 2020 to March 2, 2021, as determined by the Purposive sampling method, which yielded a sample of 241 observational samples. Secondary data in the form of time series were used in the study, and they were measured using a variety of linear regression analytic methods. The study found that the Covid-19 positive instance had a significant positive effect on JCI, whereas the exchange rate had a significant negative effect. The coefficient of determination is 0.550, indicating that Covid-19 and exchange rates influence the Composite Stock Price Index by 55%, with the remaining 45% influenced by variables outside of the scope of this study.